1972
DOI: 10.1042/bj1291035
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study of baker's-yeast pyruvate kinase activated by fructose 1,6-diphosphate

Abstract: The paper reports a study of the kinetics of the reaction between phosphoenolpyruvate, ADP and Mg(2+) catalysed by yeast pyruvate kinase when activated by fructose 1,6-diphosphate and K(+). The experimental results indicate that the reaction mechanism is of the Ordered Tri Bi type with the substrates binding in the order phosphoenolpyruvate, ADP and Mg(2+). Direct phosphoryl transfer takes place in the quaternary complex, with pyruvate released before MgATP. A dead-end enzyme-pyruvate complex is also indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
1

Year Published

1973
1973
1980
1980

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 23 publications
6
43
1
Order By: Relevance
“…The concentrations ofthe different species involved have been determined from the known equilibrium constants for their inter-conversions by using the method described by Macfarlane & Ainsworth (1972). This examination showed that five ADP and four phosphoenolpyruvate species are present in significant proportions at pH6.2: their identity and contributions to the sum of the free and The total Mg2" concentration contains an addition for Mg2+-bound ATP when this product is present as an inhibitor.…”
Section: Theory Substrate-level Equilibriamentioning
confidence: 99%
See 3 more Smart Citations
“…The concentrations ofthe different species involved have been determined from the known equilibrium constants for their inter-conversions by using the method described by Macfarlane & Ainsworth (1972). This examination showed that five ADP and four phosphoenolpyruvate species are present in significant proportions at pH6.2: their identity and contributions to the sum of the free and The total Mg2" concentration contains an addition for Mg2+-bound ATP when this product is present as an inhibitor.…”
Section: Theory Substrate-level Equilibriamentioning
confidence: 99%
“…We propose to determine whether the free or Mg2+-complexed forms of ADP and phosphoenolpyruvate are the true substrates of muscle pyruvate kinase, by using the test devised by Macfarlane & Ainsworth (1972). The basis of the test is to measure the reciprocal velocity as a function of Mg2+ concentration under conditions where the concentrations of different combinations of possible substrates are kept constant, and to estimate thereby the powers of Mg2+ concentration which appear in the empirical quaternary complex of the substrates, with the random dissociation of pyruvate and MgATP.…”
Section: Identification Ofsubstratesmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzymes, which have been isolated from mammalian tissues (Tietz & Ochoa, 1958;Irving & Williams, 1973;Nicholas & Bachelard, 1974) (Reynard et al, 1961;Ainsworth & MacFarlane, 1973), an ordered addition of substrates and dissociation of products, for the yeast enzyme (MacFarlane & Ainsworth, 1972) and a Ping-Pong mechanism involving a phosphoenzyme for the liver L-type enzyme (MacFarlane & Ainsworth, 1974). There are difficulties, however, in the interpretation of initial-velocity studies, and we are therefore studying the mechanism of these enzymes with a variety of techniques, including flux measurements with labelled substrates (Britton, 1966;, isotope-trapping (Rose et al, 1974), binding and initial-velocity studies.…”
mentioning
confidence: 99%